A Decomposition of Austria's General Government Budget into Structural and Cyclical Components - Serguei Kaniovski; Hans Pitlik; Sandra Steindl; Thomas Url (Austrian Institute of Economic Research (WIFO), 2008)
The paper describes a model for computing the trend output and the structural budget deficit in Austria. The calculation of trend output is based on a production function approach within a small macroeconomic model of the Austrian economy. A decomposition of public budgets into cyclical and structural components shows responsiveness to business cycle variations, and allows a better assessment of the sustainability of the budget balance. The model will be used in future forecasting rounds and links macroeconomic and budgetary variables of the WIFO Economic Outlook to estimates for trend output and the structural budget deficit. Until now, such decomposition has not been part of the regular WIFO forecast.
Keywords: 330; Austria; WIFO forecast; WIFO Economic Outlook; trend output; structual budget balance; Haushaltsdefizit; Prognoseverfahren; Dekompositionsverfahren; Theorie; Österreich